Spatial Development of Russia and the USA in the 16-20th centuries as formation of the major unit of geopolitical constructs of modernity - Baklanov, P.Ia. (2020)
The article considers the spatial development of Russia and the United States and their geopolitical relations in the 17-20th centuries. It is noted that the movement of Russia to the east and the United States to the west occurred nearly simultaneously and led them to their territorial rapprochement on the shores of the Pacific Ocean. The spatial development issues that were resolved during this process became milestones in the formation of the geopolitical structures of our time, and are of great importance for the fate of not only both countries, but also the world. It is stated that during the entire period under review, up to the end of the 1980s, territorial relations between them were the most stable component.